ANALISA PERBANDINGAN NPHR SAAT MILL E IN SERVICE DAN OUT SERVICE - Arifia Ekayuliana; Jusafwar Jusafwar; Diah Purwati Ningsih; Fitria Annisa (Politeknik Negeri Jakarta, 2018)
ABSTRACTCoal feeder is the main equipment in steam power plant which serves to adjust the flow rate of coal coming into the mill to be crushed. Disturbance in one of the coal feeder makes Pulverizer/Mill E supposed to operate in the event of an emergency must finally be in service status. The operation of Mill E will make a significant increase in Spray Superheater and Spray Reheater cause of overheat in the boiler convection area. Realized monthly NPHR generating performance is always different from the monthly Performance Test result due to the decreasing unit performance which comes from the increase of heat rate value that resulting in the increasing amount of coal consumption and the variability losses. To reduce the NPHR to make the plant more efficient then used NPHR calculation method that is heat losses method according to standard ASME PTC (The American Society of Mechanical Engineers Performance Test Code) with the number of parameters are more detail. So the calculated of value NPHR will have accuracy according to the actual condition. The purpose of this analysis is to analyze the performance of PLTU Labuan (Banten) which has a capacity of 2x300 MW throughout 2018 and compare it during normal conditions or when there is interference due to malfunction one of the components. The calculation of NPHR (Net Plant Heat Rate) by calculating Turbine Heat Rate, Boiler Efficiency, generator output power and self power consumption. The result of calculation with Heat Balance Method, plant has NPHR equal to 2604,190411 kcal/kWh with coal flow consumption equal to 187,38377414 Ton / h and boiler efficiency equal to 83,98% when Mill E in service and NPHR equal to 2562,130235 kcal / kWh with coal consumption equal to 178,208018 Ton/h and boiler efficiency equal to 84.23% when Mill E out service. It is known that NPHR when Mill E in service is greater than when Mill E out service which mean when Mill E operates a decrease in power plant performance and more wasteful coal consumption. With the calculation of Net Plant Heat Rate routinly and optimally can be done and fast performance can be selected.Keywords: Plant Heat Rate, NPHR, Heat Balance Method, PLTU, thermal energyABSTRAKCoal feeder merupakan peralatan utama pada PLTU yang berfungsi mengatur laju aliran batu bara yang masuk ke mill untuk dihaluskan. Coal feeder bertugas mengatur banyak sedikitnya batu bara sesuai dengan kebutuhan yang diinginkan, yakni besarnya daya yang ingin dibangkitkan dari suatu sistem PLTU. Gangguan di salah satu coal feeder membuat Pulverizer/Mill E yang seharusnya beroperasi saat darurat akhirnya harus berada dalam status in service. Beroperasinya Mill E akan membuat kenaikan yang signifikan pada Superheater Spray dan Reheater Spray akibat overheat di area konveksi boiler. Realisasi kinerja NPHR (Net Plant Heat Rate) bulanan pembangkit selalu berbeda dengan hasil Performance Test bulanan yang disebabkan oleh faktor penurunan perfoma unit akibat kenaikan nilai heat rate yang berakibat pada meningkatnya jumlah konsumsi batubara dan variability lossess. Untuk menurunkan NPHR agar pembangkit lebih efisien maka digunakan metode perhitungan NPHR yaitu metode heat losses yang sesuai standard ASME PTC (The American Society of Mechanical Engineers Performance Test Code) dengan jumlah parameter yang lebih banyak dan detail. Sehingga nilai NPHR hasil perhitungan akan memiliki keakuratan sesuai dengan kondisi sebenarnya. Tujuan dari analisa ini adalah untuk menganalisis kinerja PLTU Labuan (Banten) yang mempunyai kapasitas 2x300 MW sepanjang tahun 2018 dan membandingkannya saat kondisi normal maupun saat ada gangguan akibat tidak berfungsinya salah satu komponen. Perhitungan NPHR dilakukan dengan menghitung Turbine Heat Rate, Efisiensi Boiler, daya keluaran generator dan daya pemakaian sendiri. Hasil perhitungan dengan Metode Kesetimbangan Energi, pembangkit memiliki NPHR sebesar 2604,190 kcal/kWh dengan konsumsi batubara sebesar 187,383 Ton/h dan efisiensi boiler 83,98% saat Mill E in service dan NPHR sebesar 2562,130 kcal/kWh dengan konsumsi batubara sebesar 178,208 Ton/h dan efisiensi boiler 84,23% saat Mill E out service. Diketahui bahwa NPHR saat Mill E in service lebih besar dibanding saat Mill E out service yang berarti saat Mill E beroperasi terjadi penurunan performa pembangkit dan konsumsi batubara yang lebih boros. Dengan perhitungan Net Plant Heat Rate secara rutin dan berkala diharapkan kinerja dan performa pembangkit dapat selalu terpantau dan penyebab gangguan bisa cepat terdekeksi.Kata kunci : Plant Heat Rate, NPHR, Metode Kesetimbangan Energi, PLTU, efisiensi thermal